2017
DOI: 10.1148/rg.2017160059
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT Pitfalls in Gynecologic and Genitourinary Oncologic Imaging

Abstract: The role of whole-body positron emission tomography (PET)/computed tomography (CT) with fluorodeoxyglucose ( FDG fluorodeoxyglucose ) is now established in the assessment of many gynecologic and genitourinary malignant tumors. FDG fluorodeoxyglucose PET/CT has been widely adopted for staging assessments in patients with suspected advanced disease, in cases of suspected disease recurrence, and for determining prognosis in a number of malignancies. A number of pitfalls are commonly encountered when reviewing FDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 54 publications
0
49
0
2
Order By: Relevance
“…It has been generally accepted that 18F-FDG-PET/CT has higher diagnostic performance than CT or MRI in detecting metastatic lymph nodes in gynecological cancer patients 26 . Although it has been reported that 18F-FDG-PET/CT reliably detects lymph node deposits with a volume larger than 80 mm 3 27 , false-positive detection of lymph node involvement has been caused by benign conditions, including systemic inflammation, infectious diseases, or immunizations 28 . In our patients, false- 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been generally accepted that 18F-FDG-PET/CT has higher diagnostic performance than CT or MRI in detecting metastatic lymph nodes in gynecological cancer patients 26 . Although it has been reported that 18F-FDG-PET/CT reliably detects lymph node deposits with a volume larger than 80 mm 3 27 , false-positive detection of lymph node involvement has been caused by benign conditions, including systemic inflammation, infectious diseases, or immunizations 28 . In our patients, false- 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in human medicine have shown that necrotic masses, in particular metastatic lymph nodes, will have a falsely lowered SUV max secondary to partial volume effects as they have only a thin, metabolically active periphery. 18,28,29 Grade of mast cell tumor was significantly associated with mitotic index, Ki-67 expression, and c-Kit mutation status of exons, all of which have been shown to be related to prognosis. 26 As a secondary aim, evaluation of the utility of F18 FDG PET-CT for clinical staging in comparison to traditional methods was also evaluated.…”
Section: Discussionmentioning
confidence: 98%
“…However, in this case it may also be due in part to the large necrotic component that was noncontrast enhancing and relatively non‐avid. Studies in human medicine have shown that necrotic masses, in particular metastatic lymph nodes, will have a falsely lowered SUV max secondary to partial volume effects as they have only a thin, metabolically active periphery …”
Section: Discussionmentioning
confidence: 99%
“…There are two possible explanations. First, an over interpretation of the inflammatory or physiological 18 F-FDG accumulation as cancerous lesions is possible [23].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of 18 F-FDG near the bowel loops in etPET/CT is especially challenging [23]. Physiological bowel uptake is a common finding, which can complicate the interpretation of the metabolic response of the preoperatively detected tumour in the same anatomic area (Figure 2a).…”
Section: Discussionmentioning
confidence: 99%